Towards the Sustainability of an Oil Refinery: A Synergy between ISO 50001 and ISO 14001 Management Systems - Chaves Almanza, Fabio Daniel (International Journal of Renewable Energy Development, 2025)
The most implemented standards worldwide for Energy Management Systems (EnMS) and Environmental Management Systems (EMS), ISO 50001 and ISO 14001 respectively, maintain a close correspondence due to the Harmonized Structure (HS) recently established by the International Organization for Standardization (ISO). However, achieving greater energy efficiency does not always align adequately with environmental issues, which is most evident in fossil fuel-based industries. Therefore, this work aims to explore a synergy between these standards and use it to evaluate a technological change in an oil refinery, for better energy performance and especially environmental sustainability. The results show that the change in technology increases electric efficiency from 14% to 45% and the rate of atmospheric emissions per unit of energy generated decreases by 15% on average. However, as fuel consumption doubles, the total emission rises by about 100%. This conflict between energy and environmental performance leads to an analysis of sustainable resource management to better understand the relevance of the change in technology as an appropriate solution for the refinery in the gradual transition to clean energy. The findings of this work shed light on how to deal with oil refineries in the global landscape of urgent sustainable development.